PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH HIDROKARBON SISWA MELALUI MODEL SAVI DISERTAI MEDIA PUZZLE - Dewi, Citra Ayu; Pahriah, Pahriah; Gazali, Zulkarnain (IKIP Mataram, 2020)
Studying hydrocarbon material requires ability in problem solving so students are able to identify, analyze, and describe abstract chemical concepts and principles into concrete. The purpose of this study was to the improving of students' hydrocarbon problem solving abilities through the SAVI learning model assisted by puzzle media. The research design used in this study was pre-experimental with a research design namely One Group Pretest-Posttest Design.The study was conducted at SMAN 7 Mataram, Jl. Adi Sucipto, Ampenan Utara, Kec. Ampenan, Mataram City, West Nusa Tenggara. The subjects of this study were students of class XI Science. The research instrument include syllabus, lesson plans, worksheets, and multiple choice test items. Data were analyzed using the N-Gain test to find out the increased ability to solve hydrocarbon problems. The results showed that the level of N-Gain was in the range of 0.33 with a moderate category which meant an increase in students' problem solving abilities after using the SAVI model assisted by puzzle media. Thus, it can be concluded that students' problem solving abilities can be improved through the application of SAVI learning models assisted by puzzle media.